2021
DOI: 10.1021/acs.macromol.1c01740
|View full text |Cite
|
Sign up to set email alerts
|

Aldol Polymerization to Construct Half-Fused Semiconducting Polymers

Abstract: Conventional conjugated polymer synthesis involves costly transition-metal catalysts and even toxic reagents, causing serious environmental challenges around the world. The comonomer linkages of semiconducting polymers are mostly single bonds; charge delocalization and transport have been hindered due to rotation around these single bonds, leading to energetic and conformational disorders. Here, we have developed a novel programmable half-fused polymer library by introducing aldehyde chemistry to promote a ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…[37,41] NB has become a robust building block for constructing ladder-type rigid polymers and donor-acceptors polymers. [42][43][44][45] Rhodanine is also a strong electron withdrawing unit due to the ketone and thioketone groups on the five-membered aza ring, which have been widely utilized as the terminal groups for non-fullerene acceptors for OPV. [46,47] Herein, to achieve efficient mixed ionic and electronic small molecules conduction in OECTs, we design and synthesize two novel small molecule semiconductors with a highly electron-deficient acceptor-acceptor (A-A) system comprised of lactam and ketone in a favorable fashion.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…[37,41] NB has become a robust building block for constructing ladder-type rigid polymers and donor-acceptors polymers. [42][43][44][45] Rhodanine is also a strong electron withdrawing unit due to the ketone and thioketone groups on the five-membered aza ring, which have been widely utilized as the terminal groups for non-fullerene acceptors for OPV. [46,47] Herein, to achieve efficient mixed ionic and electronic small molecules conduction in OECTs, we design and synthesize two novel small molecule semiconductors with a highly electron-deficient acceptor-acceptor (A-A) system comprised of lactam and ketone in a favorable fashion.…”
Section: Research Articlementioning
confidence: 99%
“…[ 37,41 ] NB has become a robust building block for constructing ladder‐type rigid polymers and donor–acceptors polymers. [ 42–45 ] Rhodanine is also a strong electron withdrawing unit due to the ketone and thioketone groups on the five‐membered aza ring, which have been widely utilized as the terminal groups for non‐fullerene acceptors for OPV. [ 46,47 ]…”
Section: Introductionmentioning
confidence: 99%
“…20,21 In contrast, the emergence of metal-free catalyzed polymerization has offered a promising approach for the synthesis of conjugated polymers (Scheme 1a). [22][23][24][25][26] The acid-catalyzed aldol polymerizations for the synthesis of isoindigo-derived conjugated polymers have gained attention in recent years. [22][23][24][26][27][28][29][30][31] For example, McCulloch and co-workers have reported the p-toluene sulphonic acid-catalysed aldol polymerization for the synthesis of five electron-deficient rigid polymers in good yields.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] The acid-catalyzed aldol polymerizations for the synthesis of isoindigo-derived conjugated polymers have gained attention in recent years. [22][23][24][26][27][28][29][30][31] For example, McCulloch and co-workers have reported the p-toluene sulphonic acid-catalysed aldol polymerization for the synthesis of five electron-deficient rigid polymers in good yields. 22 The route is environmentally benign with water as the by-product.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 A common strategy to obtain soluble organic semiconductors is to install flexible alkyl side-chains on the p-conjugated molecular framework. 27,28 Importantly, the incorporation of alkyl side-chains can dramatically affect the charge transport properties of organic semiconductors in the solid state by tailoring the intermolecular interaction and the molecular packing motif. For instance, we have demonstrated that dithiophene-4,9-dione derivatives can exhibit a transition between unipolar and ambipolar charge transport behaviours depending on the length of the side-chains, 29 while attaching heteroatom-linked alkyl chains may increase the carrier mobility up to several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%